Stock And Business Valuation Of Indonesian Real Estate Company Post Covid-19 Pandemic (Sinarmas Land Ltd.) - Nadhifian Reksoprodjo, Risyad; Aswin Rahadi, Raden (Fakultas Ekonomi Universitas Gresik, 2023)
The real estate industry in Indonesia has been a key driver of the country’s development and economic growth and has seen sustained growth throughout the years. However, challenges do exist in the industry, ranging from oversaturation of products in the market, to temporary lowered demand due to the Covid-19 pandemic. Despite these challenges, the sector is still very promising and expected to grow rapidly in the coming years. Investing into this industry could be a viable venture, and one of the ways to do it is to invest in one of Indonesia’s real estate developers such as Sinarmas Land Ltd, one of the largest development corporations in Indonesia. Before investing into the company, it is vital to study and do due diligence on the market and the company itself, and that is the goal of this journal, which presents a comprehensive valuation analysis of Sinarmas Land Ltd (A26:SGX), which employs financial ratio analysis, absolute valuation using the Discounted Cash Flow (DCF) method, and relative valuation using the Price to Equity Ratio (PER) and Enterprise Value to EBIDTA (EV/EBITDA) method. This study will be valuable to potential investors, analysts, and industry participants seeking to make informed decisions and capitalize on the opportunities presented by the Indonesian real estate sector